Accumulation of radiolabelled platelets and fibrin on the carotid artery of rabbits after angioplasty: effects of heparin and dipyridamole - van Ryn, Joanne; Lorenz, Martin; Merk, Herbert; Buchanan, Michael R.; Eisert, Wolfgang G. (Thrombosis and Haemostasis, 2003)
We investigated the dynamic accumulation of platelets and fibrin after balloon injury of the carotid arteries in rabbits in vivo. In addition, effects of heparin and dipyridamole treatment were also tested. Autologous 99mTc-labelled platelet and 123I-labelled fibrin accumulation was measured at one minute intervals for 4 hours following balloon injury of the carotid artery. Platelet accumulation occurred rapidly, with a ~125% increase occurring within 30 min after injury. There was no further activity for up to 4 hours. This accumulation could be inhibited with an intravenous infusion of PGI2 (500 ng/kg/hr). Fibrin accumulation occurred slowly and continuously over the 4 hour measurement period. Injection of an anti-fibrin antibody inhibited fibrin accumulation. Heparin (25 U/kg/hr for 4 hrs) administration resulted in a significant 82 ± 19% and 68 ± 13% reduction in platelet and fibrin accumulation, respectively. This dose of heparin was associated with a 2-fold prolongation of the aPTT. Dipyridamole (0.45 mg/kg/hr for 4 hrs) resulted in a 46 ± 12% and 70 ± 25% reduction of platelet and fibrin accumulation, respectively. Thus, we demonstrated that the dynamics of platelet and fibrin accumulation following balloon injury in rabbits are very different. The vessel wall continues to be thrombogenic for fibrin up to 4 hours after injury even though platelet accumulation has ceased after one hour. We conclude that the local thrombotic events following balloon injury are complex and that not only platelets but also fibrin is important in regulating responses to injury.
Keywords: Animal models; platelet pharmacology; fibrin; vascular injury; dipyridamole